CAKE: An Efficient Group Key Management for Dynamic Groups - Hillmann, Peter; Knüpfer, Marcus; Guggemos, Tobias; Streit, Klement (INFOCOMP Journal of Computer Science, 2019)
With rapid increase of mobile computing and wireless network linkage, the information exchange between connected systems and within groups increases heavily. Exchanging confidential information within groups via unsecured communication channels is a high security threat. In order to prevent third parties from accessing this data, it is essential to encrypt it. For this purpose, the group participants need a common group key to enable encrypted broadcast messages. But efficient key management of secured group communication is a challenging task, if participants rely on low performance hardware and small bandwidth. For coordination and distribution, we present the modular group key management procedure CAKE that is centrally organized and meets strict security requirements. The lightweight G-IKEv2 protocol in combination with the key exchange concept of CAKE leads to an efficiently integrated solution. The hybrid approach combines the advantages of the existing protocols with the objective to reduce the computation and communication effort. It is shown that the procedure is more suitable for changing MANET groups than the existing ones. Moreover, the exchanged group key can be used for any services which provides a wide range of applications.